Reading Hebrews in context : the sermon and Second Temple Judaism - Blackwell, Ben C., 1974-; Goodrich, John K., 1981-; Maston, Jason., 1978- (Grand Rapids : : Zondervan Academic, 2023)
"Reading Hebrews in Context brings together short, accessible essays that compare and contrast the theology and hermeneutical practices of the book of Hebrews with early Jewish literature"--
Philo of Alexandria and Hebrews 1:1-14: The Firstborn and Image of God / Angela Costley -- 4 Ezra and Hebrews 2:1-9: Suffering and God's Faithfulness to His Promises / Fľix H. Cortez -- Jubilees and Hebrews 2:10-18: Passover and the Defeat of the Devil / David M. Moffitt -- Wisdom of Solomon and Hebrews 3:1-19: The Spirit of Wisdom as a Guide through the Desert / Madison N. Pierce -- Josephus and Hebrews 4:1-13: The Promise of Entering God's Rest / Bryan J. Whitfield -- Sirach and Hebrews 4:14-5:10: Called to Be High Priest, Just Like Aaron / Bryan R. Dyer -- Community Rule and Hebrews 5:11-6:12: Perfection, Perseverance, and Apostasy / John K. Goodrich -- Philo of Alexandria and Hebrews 6:13-20: The Purpose of the Divine Oath / Dana M. Harris -- 11Q Melchizedek and Hebrews 7:1-10: The Heavenly Melchizedek / Eric F. Mason -- Damascus Document and Hebrews 7:11-28: Messianism and the Aaronic High Priesthood / Dominick S. Hernandez -- Damascus Document and Hebrews 8:1-13: The New Covenant / Radu Gheorghita -- Philo of Alexandria and Hebrews 9:1-10: The Passing and the Permanent / Kenneth L. Schenck -- Songs of the Sabbath Sacrifice and Hebrews 9:11-28: Heavenly Sanctuary, Priest, and Sacrifice / Benjamin Ribbens -- Philo of Alexandria and Hebrews 10:1-18: The Sacrifices of the Righteous / Zoe O'Neill -- Mishnah Yoma and Hebrews 10:19-39: Deliberate Sin and Atonement / Jason Maston -- 2 Maccabees and Hebrews 11:1-22: Faith, Creation, and Resurrection Hope / Matthew C. Easter -- Biblical Antiquities and Hebrews 11:23-40: Israel's History as a Call to Faith / Susan Docherty -- Psalms of Solomon and Hebrews 12:1-17: The Paternal Discipline of God / Amy Peeler -- Samaritan Pentateuch and Hebrews 12:18-29: Moses on the Mountain / Michael H. Kibbe -- Philo of Alexandria and Hebrews 13:1-25: Meeting the Forgiving God Outside the Camp / Gabriella Ardini.
Includes index.
Description based on print version record and CIP data provided by publisher
Keywords: Bible. -- Criticism, interpretation, etc; Judaism (Christian theology) -- Biblical teaching; Judaism -- Relations -- Christianity